Ethyl 3-methyl-1-oxo-4H-1,4-benzothiazine-2-carboxylate monohydrate - Yamna Baryala; Youness El Bakri; El Hassane Anouar; Abdelfettahb Zerzouf; El Mokhtar Essassi; Joel T. Mague (IUCrData, 2018)
The organic molecule in the title hydrate, C12H13NO3S·H2O, is folded across the S...N vector. Chains two molecules thick extending along the a-axis direction are formed by N—H...O and O—H...O hydrogen bonds. These interactions are reinforced by C—H...S hydrogen bonds and offset π-stacking interactions between centrosymmetrically related benzene rings. The chains are associated through C—H...O hydrogen bonds.